Edukacja inkluzyjna uczniów z niepełnosprawnością wzroku – w kręgu wizji utopijnych (?) - Czerwińska, Kornelia (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The first part of the article is focused on mail theoretical principles of inclusive education. Inclusive education is an ideal model of a school system in which education offer is flexibly adjusted to psycho-physical capabilities and educational and developmental needs of all students who constitute a heterogenous group. Any personal and environmental features of students which make them a heterogenous team (e.g. gender, impairment, talents, being a member of a national or ethnic minority, low material status of the family, etc.) can potentially become an educational barrier which is removed due to proper organization of school functioning. The concept of educating students in inclusive groups, i.e. groups of different students with equal rights, whose relations are based on cooperation and mutual assistance, not on subordination and competition, is rather a utopian vision. The second part of the text discusses the specific situation of students with visual impairment in the context of the utopian concept of inclusion.
Keywords: education; inclusion; utopia; visual impairment